Los Angeles sentinel ([Los Angeles, Calif.] : Leon H. Washington, Jr, 1933)
The Los Angeles Sentinel is an African American owned and operated newspaper that puts emphasis on issues concerning the African-American community and it's readers. Its a highly regarded paper that significantly influences the perceptions, attitudes and buying decisions of it's readership.
Mode of access: World Wide Web.
Description based on: Vol. 2, no. 1 (May 1934); title from digitized issue running title (ProQuest, viewed Feb. 7, 2011).
Latest issue consulted: Vol. 521, no. 41 (Dec. 29 [2004]/Jan. 4 2005) (ProQuest, viewed Feb. 7, 2011).
Keywords: African Americans -- California -- Los Angeles -- Newspapers; African Americans; Los Angeles (Calif.) -- Newspapers; Los Angeles County (Calif.) -- Newspapers; California -- Los Angeles; California -- Los Angeles County; Electronic journals